Formative assessment as practice: the role of students' motivation. Issue 2 (17th February 2021) - Leenknecht, Martijn; Wijnia, Lisette; Köhlen, Martine; Fryer, Luke; Rikers, Remy; Loyens, Sofie
Abstract: Formative assessment can be seen as an integral part of teaching and learning, as formative assessment affects students' learning and vice versa. Students' motivation can theoretically be placed at the centre of this reciprocal relationship, as formative assessment is assumed to affect students' need satisfaction of autonomy, competence and relatedness, and consequently their autonomous motivation. In the current study, two assumptions were tested empirically: formative assessment contributes to students' autonomous motivation and students' need satisfaction functions as a mediator in this relationship. The results provided support for those assumptions and indicated that more perceived use of formative assessment is associated with more feelings of autonomy and competence, and more autonomous motivation. The current study demonstrated the benefits of studying formative assessment as practice and provides encouragement for teachers to start applying formative assessment in their classroom. The theoretical model provides teachers with guidelines for an optimal implementation of formative assessment and provides researchers with a framework to study the phenomenon of 'formative assessment as practice' in more depth.